2021
DOI: 10.1177/15330338211058352
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Detected by Machine Learning Models Using Conventional Laboratory Test Data

Abstract: Background: Current diagnostic methods for colorectal cancer (CRC) are colonoscopy and sigmoidoscopy, which are invasive and complex procedures with possible complications. This study aimed to determine models for CRC identification that involve minimally invasive, affordable, portable, and accurate screening variables. Methods: This was a retrospective study that used data from electronic medical records of patients with CRC and healthy individuals between July 2017 and June 2018. Laboratory data, including l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 33 publications
(68 reference statements)
0
14
0
Order By: Relevance
“…A retrospective study in China stated that MPV-to-platelets ratio was used as an effective diagnostic index to distinguish benign from malignant CRC and distinguish early CRC from advanced CRC [ 19 ]. Hui et al [ 21 ] found that CEA, Hb, lipoprotein (a), and high-density lipoprotein might be powerful and noninvasive diagnostic indicators based on machine-learning approaches. Consistently, we have studied the diagnosis of CRC by hematological indicators, and there is also agreement on diagnostic indicators such as platelet-related parameters and CEA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study in China stated that MPV-to-platelets ratio was used as an effective diagnostic index to distinguish benign from malignant CRC and distinguish early CRC from advanced CRC [ 19 ]. Hui et al [ 21 ] found that CEA, Hb, lipoprotein (a), and high-density lipoprotein might be powerful and noninvasive diagnostic indicators based on machine-learning approaches. Consistently, we have studied the diagnosis of CRC by hematological indicators, and there is also agreement on diagnostic indicators such as platelet-related parameters and CEA.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, carcinoembryonic antigen (CEA) is a common tumor marker that has assisted in the diagnosis of CRC [ 20 ]. A machine-learning model using biochemical and hematological markers was built to identify CRC patients [ 21 ]. Several studies have established models of diagnosing CRC based on inflammation factors, platelet-related markers, or CEA [ 22 , 23 ], but most studies have excluded people with inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the simple form of the LR model (very similar to the linear model), it is difficult to fit the real distribution of data, so the accuracy is not high. Therefore, the LR model is currently widely used to predict the factors of disease pathogenesis [ 77 , 83 ]. We can use the LR model to analyze and predict disease risk through clinical laboratory testing items.…”
Section: Discussionmentioning
confidence: 99%
“…Li also used laboratory data, including liver enzymes, lipid profiles, complete blood counts, and tumor biomarkers to develop five machine learning models to identify colorectal cancer (CRC). The results showed that the logistic regression model achieved the highest performance in identifying CRC (AUC: 0.865, sensitivity: 89.5%, specificity: 83.5%, PPV: 84.4%, NPV: 88.9%) [ 83 ]. Studies of Clinlabomics in diagnosing disease have increased, both in general and severe diseases, and have achieved remarkable diagnostic results.…”
Section: The Application Of Clinlabomicsmentioning
confidence: 99%
“…Currently, colonoscopy is considered the gold standard tool for CRC detection; however, invasive procedures and complications preclude its widespread implementation [ 3 ]. Compared to colonoscopy, blood-based tumor biomarkers such as carcinoembryonic antigen (CEA) and carbohydrate antigen 19–9 (CA19-9), are widely used because they are noninvasive but show unsatisfactory performance [ 4 ]. Therefore, investigations of novel biomarkers, especially blood-based biomarkers for the early diagnosis of CRC, are highly warranted.…”
Section: Introductionmentioning
confidence: 99%